4x^2 + 5x - 6 = (4x - 3) (x + 2)
You can do it by using the quadratic function to solve 4x^2 + 5x - 6 = 0; the result will be x = 3/4 and x = -2
Then you have to make (x- 3/4) = 0 and (x +2 ) = 0
When you develop x - 3/4 = 0 you get 4x -3 = 0, which means that 4x - 3 is a factor. The other factor is directly x + 2.
Answer: option b: (4x -3)(x + 2)
Yes by 10's and hundreds and ones place and even and odd. And pine and composite
Vas happening?
You break it down
3 ^5 is 3 x 3 x 3 x 3 x 3 = 729
4 ^ 5 is 4 x 4 x 4 x 4 x 4 = 1024
729 times 1024 = 746,496
12 ^ 10 is 12 x 12 x 12 x 12 x 12 x 12 x 12 x 12 x 12 x 12 = 6.19174e10
So the answer is incorrect
You must distribute first, so 3(8p+7r). That will equal 24p +21r. Then you must add all the values together according to like terms, so the variables must match. So simplified it will be 22+24p+30r